Prinsip Perancangan Kawasan Tepi Air (Kasus: Kawasan Tanjung Bunga) - Isfa Sastrawati (Journal of Regional and City Planning, 2003)
Waterfront area could be a part of city that is very potential to become a livable area and a meeting place for its citizens. The development in the area has to be controlled with waterfront design principles. These design principles are built based on physical characteristics, natural environment, the impact of the development, existing problems, not only considered on land use efficiency. This study is aimed at creating waterfront design principles and proposing to implement the principles in Tanjung Bunga. In order to design principles, issues of concern and scope of issues in waterfront city must be identified. The design principles are prepared to develop a livable, imageable and enduring waterfront area. Waterfront design principles are built with consideration to fulfill the human needs in public space, pedestrian way, view, the potentials and the uniqueness of the area. The principles which are buolt in this study can be used as principal guidelines of the development, especially in Tanjung Bunga.Keywords: design principles, waterfront city, waterfront characteristics, issues of concern, scope of issues